Feed the need 1.0 - Idham, Muhammad Aidil (Faculty of Medicine, 2021)
The COVID19 pandemic that was started in December 2019 has given a significant impact on the social economy, health, welfare and most importantly on the survival of the people, especially for our beloved Malaysians. One after another MCO extension has understandably heightened levels of anxiety, fear and distress among Malaysians. Thousands of businesses have been shuttered or badly affected and many have lost their incomes, jobs and loved ones to the Covid-19 pandemic, with seemingly little to no help or silver lining in sight.